1978
DOI: 10.1530/acta.0.0890089
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Heterogeneity in Lung Cancer and Medullary Thyroid Cancer

Abstract: An investigation was made of the increased serum calcitonin in patients with medullary thyroid cancer and bronchogenic carcinoma in order to determine whether these conditions can be differentiated immunochemically. Endogenous fractions of immunoreactive calcitonin were separated by gel filtration and radioimmunoassayed with calcitonin antibodies having different region specificities. The pattern of serum heterogeneity of patients with medullary thyroid cancer was characterized by the presence of at least seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 10 publications
1
18
1
1
Order By: Relevance
“…16 Shortly thereafter, it was demonstrated that precursors of calcitonin, including PCT, were also elevated in the serum of patients with neuroendocrine tumors and could be used equally well as serum markers of cancer. 17,18 In the 1990s, increased PCT concentrations were noted in the sera of patients with severe systemic inflammatory conditions including inhalational injury in burns, 12,19 pulmonary aspiration, 20 pancreatitis, 21 and heat stroke. 22 Similar elevations in serum PCT were observed after severe mechanical trauma 23 and extensive surgery.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…16 Shortly thereafter, it was demonstrated that precursors of calcitonin, including PCT, were also elevated in the serum of patients with neuroendocrine tumors and could be used equally well as serum markers of cancer. 17,18 In the 1990s, increased PCT concentrations were noted in the sera of patients with severe systemic inflammatory conditions including inhalational injury in burns, 12,19 pulmonary aspiration, 20 pancreatitis, 21 and heat stroke. 22 Similar elevations in serum PCT were observed after severe mechanical trauma 23 and extensive surgery.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…This differs from the mature 32-amino acid CT peptide by its larger molecular weight and, hence, has been variously referred to as ''large molecular weight calcitonin'', ''precalcitonin'' or ''big calcitonin'' [29][30][31][32]. These peptides were also measurable in high levels in patients with small cell lung cancer and medullary thyroid cancer, where they have prognostic implications [33,34]. This large molecular weight material consists of several CT precursors [14,35,36].…”
Section: Assays To Measure ''Pct''mentioning
confidence: 99%
“…Medulla C‐cell‐carcinoma of the thyroid gland can by itself lead to increased serum levels of PCT as well as of calcitonin [36]. Small‐cell lung cancercan increase PCT‐ or calcitonin‐immunoreactivity [37,38].…”
Section: Introductionmentioning
confidence: 99%